Faktor - Faktor Yang Mempengaruhi Profitabilitas Pada Perusahaan Bumn Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015 – 2019 - Ryan Hansen, Herlin Tundjung (Jurnal Paradigma Akuntansi, 2021)
The purpose of this study was to determine and analyze whether the independent variables of working capital, capital structure, and good corporate governance affect profitability. This research was conducted at a state-owned company listed on the Indonesia Stock Exchange (IDX) from 2015 to 2019. The sample in this study was selected using the purposive sampling method. 15 of the 20 state-owned companies were used as research subjects. This study uses secondary data collected through the Indonesia Stock Exchange website which was processed using panel data regression analysis and Eviews application version 9.0. Based on the results of data processing, it is found that working capital, capital structure, and good corporate governance simultaneously have a significant effect on profitability. Working capital is partially positive and significant effect on profitability, capital structure is partially negative and significant effect on profitability, while good corporate governance has a positive and significant effect on profitability.